Static strength of tubular DT joints using lusas finite element software - Abd. Rahman, Norashidah (2005)
Structural tubular are widely used in the construction of offshore structures. As these structures are located in hostile environment, these joints represent structural weak spots and so it is desirable to develop reliable methods of determining their static collapse loads. This studies focus on the analysis of static strength of tubular DT joints under brace compression loading by using LUSAS finite element software. The numerical static strength result is compared with an experimental test result obtained from the literature. The value of the static strength obtained in this work is 56% lower than that of the experimental test. A parameter study was performed to study the effect of the geometric parameters u, \3, y and L as well as the effect of the yield strength cry on the static strength of DT joint model. Finally, a simple equation relating the static strength to the above parameters is proposed.